Grading student behavior - Schoner, Florian,Mergele, Lukas,Zierow, Larissa (CESifo, Center for Economic Studies & Ifo Institute, 2021)
Numerous countries require teachers to assign comportment grades rating students' social and work behavior in the classroom. However, the impact of such policies on student outcomes remains unknown. We exploit the staggered introduction of comportment grading across German federal states to estimate its causal effect on students' school-to-work transitions as well as cognitive and non-cognitive abilities. Analyzing census data, household surveys, and nationwide student assessments, we show that comportment grading does not meaningfully affect these outcomes and rule out large effect sizes. Our results are consistent with these grades being insufficiently salient for students to alter actual student behaviors.
10419/245456
Keywords: Graue Literatur; school reforms; report cards; labor market transition; student achievement